A Clinical Decision Rule Based on the AST-to-Platelet Ratio Index Improves Adherence to Published Guidelines on the Management of Acute Variceal Bleeding. Issue 7 (August 2015) - Civan, Jesse M.; Lindenmeyer, Christina C.; Whitsett, Maureen; Herrine, Steven K.
<x xml:space="preserve">Abstract</x> Background: Optimal management of acute upper gastrointestinal bleeding (UGIB) depends on identifying a variceal versus nonvariceal etiology. An objective measure predicting etiology could guide early management pending endoscopy. The AST-to-platelet ratio index (APRI) score has been studied as a marker of cirrhosis and portal hypertension, but has not been evaluated in the setting of acute UGIB. Methods: In this single-center retrospective cohort study, we reviewed endoscopy reports and other data for patients with acute UGIB, and classified episodes as variceal bleeds or other. We assessed the diagnostic utility of the APRI score relative to other objective measures by Area Under the Receiver Operating Characteristic (AUROC) curve analysis. We constructed a clinical decision rule based on the APRI score, and assessed how it would have changed management. Results: The APRI score performed well in predicting a variceal etiology of acute UGIB, with AUROC 0.89. We developed a clinical decision rule using an APRI score of 0.4 to guide early management of acute UGIB patients. Retroactively applying this to our cohort, adherence to published guidelines for administration of octreotide and antibiotics would have increased from 56% to 91%. Conclusions: The APRI score is an objective metric that helps predict a variceal etiology of acute UGIB. Using our proposed decision rule could improve adherence to guidelines on management of acute variceal bleeding. Although we were unable to demonstrate a survival benefit, improved adherence to evidence-based guidelines serves as a metric related to this most important outcome measure. Prospective study to validate these findings is indicated.